Hyperparathyroidism-Jaw Tumor Syndrome Associated to a CDC73 Gene Pathogenic VARIANT and a Nonossifying Desmoplastic Fibroma of the Mandible - Castellano Elena; Craparo Andrea; Fabrizia Di Giovanni; Linari Alessandra; Fortunato Mirella; Maffè Antonella (Case Reports in Endocrinology)
Most cases of primary hyperparathyroidism (PHPT) are sporadic and are caused by parathyroid adenomas. Hereditary forms may occur in up to 10% of PHPT patients and are more frequent in younger patients. The hyperparathyroidism-jaw tumor (HPT-JT) syndrome is characterized by PHPT in up to 95% of patients and ossifying fibromas in the jaw in 25%–50%. We describe the case of a 35-year-old male from Bangladesh referred to our hospital due to a voluminous right mandibular swelling: a rare nonossifying fibroma of the mandible was diagnosed. Due to functional impotence, a left shoulder magnetic resonance imaging (MRI) was performed with evidence of a pluri-lobulated cyst-like lesion in the proximal humeral area diagnosed as a brown tumor (BT). Subsequent tests highlighted hypercalcemia and hypophosphatemia with high PTH levels. A heterozygous CDC73 pathogenic variant c.96>A p.Trp32Ter was identified. To the best of our knowledge, this is the first reported case of HPT-JT syndrome related to a CDC73 pathogenic variant, associated to a BT of the arm and a rare nonossifying fibroma of the mandible.